A century-long trend of metal pollution in the Sheyang River, on the coast of Jiangsu (China), reconstructed from sedimentary record. Issue 1 (2nd January 2017) - Wu, Shanshan; Han, Ruiming; Yang, Hao; Wang, Qiaojia; Bi, Fengzhi; Wang, Yanhua
ABSTRACT: In order to reveal the historical context of metal element accumulation under the economic boom during the last decades in eastern China, concentrations of nine metal elements, radionuclides ( 210 Pb), Pb isotope ratios ( 207 Pb/ 206 Pb) and sedimentary characteristics were investigated in two sediment cores collected from the Sheyang River. The sediments have recorded the heavy metal deposition and thus allow establishing a connection between the temporal evolution of the heavy metal pollution and historical changes in industrial and urban discharges. Enrichment factors (EFs) were calculated to estimate the level of contamination in these sediments. A significant anthropogenic enrichment of Cu, Ni, Pb, Cr and Zn was highlighted, which were identified from anthropogenic discharges from cities and industrial sources, according to a cluster analysis. According to the annual variation in GDP growth rate, industrial growth rate, ratio of 207 Pb/ 206 Pb and EFs, it was obvious that sedimentary accumulation of metals has a close relationship with anthropogenic activities. In the pre-industrial period, natural inputs prevailed with lower EF and constant 207 Pb/ 206 Pb ratios around 0.82. However, during 1980–1995, the rapid industrial development caused a gradual increase in EFs and 207 Pb/ 206 Pb (>0.83). Our results disinterred the evolution of anthropogenic metal inputs in the last century into the Sheyang River.